Relationship between the levels of knowledge and management of production costs of the managers of the Colombian gastronomic sector (2022)
This research studies the relationship between the levels of knowledge and management of production costs with the socio-demographic variables of managers. Based on a quantitative study, an instrument on the Likert scale was applied to a group of 21 companies belonging to the gastronomic industry, in San José de Cúcuta, Colombia. The hypotheses were contrasted through an analysis of variance and a Pearson correlation analysis. The results show that there is a relationship between knowledge of direct materials and years of age of managers. Similarly, there is a correlation between knowledge and management of production costs by managers. This implies that, to the extent that managers deepen their experience on production costs, they will be able to accurately identify the cost elements of the different products, efficiently allocating economic resources.